2016
DOI: 10.1155/2016/7824321
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chronic Periodontitis and Erectile Dysfunction: A Narrative Review

Abstract: Objective. To conduct a descriptive literature review on research studies investigating the association between chronic periodontitis (CP) and erectile dysfunction (ED).Methods. Cohort studies, case-control studies, cross-sectional studies, randomized control trials, and animal studies up to July 2015 that studied the relationship between CP and ED were reviewed and reported. Data sources included PubMed, EMBASE, Cochrane Library, and Clinicaltrials.gov. The themes “periodontal disease” and “erectile dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Furthermore, evidence from recent systematic reviews[ 35 36 ] and meta-analysis[ 37 ] of available literature also revealed the positive association between CP and ED. The pooled odd-ratio of the included studies in meta-analysis[ 37 ] showed that patients with ED were 3.07-fold more likely than controls to be diagnosed with CP.…”
Section: E Vidence L Inking O mentioning
confidence: 99%
“…Furthermore, evidence from recent systematic reviews[ 35 36 ] and meta-analysis[ 37 ] of available literature also revealed the positive association between CP and ED. The pooled odd-ratio of the included studies in meta-analysis[ 37 ] showed that patients with ED were 3.07-fold more likely than controls to be diagnosed with CP.…”
Section: E Vidence L Inking O mentioning
confidence: 99%
“…La DE puede ser causada por factores orgánicos, psicogénicos o mixtos [5]. Dentro de los factores orgánicos se incluyen: la disfunción vasculogénica, neurogénica, endocrinológica, la alteración del músculo liso cavernoso, los traumas iatrogénicos y la disfunción inducida por fármacos [6,7]. Se estima que la DE se presenta con una prevalencia del 3% al 76.5% en la población masculina global, incrementando en sentido lineal en relación con la edad [8].…”
Section: Introductionunclassified
“…Evidence suggests shared risk factors between PD and ED, including diabetes, smoking, hypertension, and coronary heart disease (Oğuz et al, 2013; Shariff et al, 2016; Sharma et al, 2011; Singh et al, 2017). Literature supports a pathophysiological link between ED and PD, such as systemic inflammation, oxidative stress, and endothelial dysfunction.…”
mentioning
confidence: 99%
“…Literature supports a pathophysiological link between ED and PD, such as systemic inflammation, oxidative stress, and endothelial dysfunction. Periodontal treatment may result in an improvement of endothelial function by reducing the level of systemic biomarkers (Changal et al, 2019; Shariff et al, 2016; Singh et al, 2017). Animal studies indicated a decrease in the expression of endothelial nitric oxide synthase (eNOS) and NOS activity in penile cavernous tissue, caused by a mild systemic inflammatory status in periodontitis as a possible mechanism for the effect of periodontitis on penile erection (Zuo et al, 2011).…”
mentioning
confidence: 99%